Trade and the environment - Håkan Nordström; Scott Vaughan (World Trade Organization (WTO), 1999)
The study shows that trade could play a positive role in the diffusion of environment-friendly technologies around the world and is backed up by the five case studies on chemical-intensive agriculture, deforestation, global warming, acid rain, and overfishing.
Keywords: 330